Tribo-corrosion response of additively manufactured high-entropy alloy - Jibril Shittu (Nature Portfolio, 2021)
Abstract High-entropy alloys (HEAs) with multiple principal elements represent a paradigm shift in structural alloy design and show excellent surface degradation resistance in corrosive environment. Here, the tribo-corrosion response of laser-engineered net-shaped CoCrFeMnNi HEA was evaluated in 3.5 wt% NaCl solution at room temperature. The additively manufactured (AM-ed) CoCrFeMnNi showed five times lower wear rate, regenerative passivation, and nobler corrosion potential during tribo-corrosion test compared to its arc-melted counterpart. A significant anisotropy was seen in the tribo-corrosion response with 45° to the build direction showing better performance compared to tests along the build direction and perpendicular to it. The open circuit potential curves were characterized by a sharp drop to more negative values as wear began, followed by continuous change for the active tribo-corrosion duration and finally a jump to nobler value at the end of the test indicating excellent surface re-passivation for the AM-ed alloy. The superior tribo-corrosion resistance of AM-ed CoCrFeMnNi was attributed to the refined microstructure and highly protective surface passivation layer promoted by the sub-grain cellular structure formed during additive manufacturing. These results highlight the potential of utilizing additive manufacturing of HEAs for use in extreme environments that require a combination of tribo-corrosion resistance, mechanical durability, extended service life, and net shaping with low dimensional tolerance.